Optimisation for accuracy improving of MSB signal detection. Issue 24 (1st November 2017) - Ye, Yunfei; Wang, Ping; Wu, Ning; Ge, Fen; Zhou, Fang
Abstract : Aimed to eliminate the lift‐off effect on the accuracy of the result of Barkhausen noise detection, this Letter simulated three conditions of the yoke by Ansoft. After studying the simulation results, it proposed a new sensor structure, utilising the mechanical structure of the spring to eliminate the lift‐off of the pick‐up coil and the BP neural network was adopted to optimise the detected magnetic Barkhausen noise characteristic value. At last, it verifies that the detection error caused by the lift‐off of the sensor is reduced effectively.